2015
DOI: 10.1176/appi.ps.201400224
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Safe Driving Practices Among Consumers of Mental Health Services: Guidelines for Assessment

Abstract: Driving is often omitted or ignored during assessment and ongoing work with consumers of mental health services. This Open Forum describes guidelines to help providers of psychiatric services to support safe driving practices among consumers. The guidelines were developed over seven years with contributions from a wide range of stakeholders. They include key principles for conducting screening and initial assessment, obtaining a detailed driving history, and performing risk assessment. The guidelines include i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Immediate contraindications to driving include acute psychosis, a relapse occurs, a sedating medication is initiated or the dose is increased, or if there is a lack of insight or cooperation with treatment, a suicidal plan involving crashing a vehicle, or intent to use a vehicle to harm others. Although similar to others found internationally (Dun et al., 2015b), these guidelines provide only general parameters; quantification, integration, and practical assessment of these factors remains difficult.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Immediate contraindications to driving include acute psychosis, a relapse occurs, a sedating medication is initiated or the dose is increased, or if there is a lack of insight or cooperation with treatment, a suicidal plan involving crashing a vehicle, or intent to use a vehicle to harm others. Although similar to others found internationally (Dun et al., 2015b), these guidelines provide only general parameters; quantification, integration, and practical assessment of these factors remains difficult.…”
Section: Introductionmentioning
confidence: 76%
“…“Occupational therapists are experts in the relationship between occupation, health, and well-being” (Unsworth, 2010). Internationally, occupational therapists have been identified as being the ideal health professionals to screen and assess driving ability (Asimakopulos et al., 2012; Dun et al., 2015b; Ménard and Korner-Bitensky, 2008; Ménard et al., 2012; Unsworth, 2010). The occupational therapy focus on function and the impact of cognitive, perceptual, psychosocial, physical, and environmental factors on occupational performance provides a solid basis for these assessments (Ménard et al., 2012; Pellerito and Davis, 2005; Unsworth et al., 2005; Unsworth, 2010; Vrkljan et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Audit reports have also shown that driving and license status of drivers with mental illness is not routinely addressed by clinicians in their case management (Orr & Elworthy, 2008;Yaqub, Ismail, Babiker, & Rao, 2016). Dun, Bull et al (2015) even explicitly commented that 'driving is often omitted or ignored during assessment and ongoing work with consumers of mental health services' (p. 536). This may be due to the low confidence of clinicians in determining client's fitness-to-drive (Marshall, Demmings, Woolnough, Salim, & Man-Son-Hing, 2012).…”
Section: Need For Evaluation Of Drivers With Mental Illnessmentioning
confidence: 99%
“…• Not applicable provided by occupational therapists specialised in mental health practice and with recognised training in driving assessment (Dun, Baker et al, 2015;Dun, Bull et al, 2015). Driving assessment is imbedded in occupational therapy practice.…”
Section: Schizophreniamentioning
confidence: 99%
See 1 more Smart Citation